Die deutschen Weinbaugebiete. Regionale Differenzierung in der Entwicklung der Rebflächen und der Betriebsstruktur 1949 bis 1960 - Hahn, Helmut (ERDKUNDE, 1968)
The economic developments of post war years have led to deep-seated structural changes in German agriculture, which have also affected viticulture. Available data shows a trend towards concentration on vine cultivation and towards larger enterprises, but this trend is not equally strong in all areas and also does not always move in the same direction. In general, a contrast between the wine growing areas of the north-west and those of the south west can be recognised. While in the Rhineland viticulture areas, especially the Mosel, Rheingau, Nahe, Rheinhessen and Rheinpfalz singleproduct wine enterprises are the rule, coupled only in Rheinhessen with other special crops, the south-west, especially Württemberg and Franconia, but also parts of Baden, has maintained the older type of farmer/ wine-producer enterprise. The cartograms of wine Kreise show in detail spatial differentiation in the development of vineyard area, numbers of wine-producing enterprises, the relationship between vine area and other agricultural land uses and the average vine area per enterprise. Changes in enterprise structure in selected wine Kreise between 1949 and 1960 are also shown. These diagrams confirm the concentration of viticulture into a few core areas and show a picture of different structure in the peripheral and collapse phenomena of the contracting areas. In the core areas, total vine area and that per enterprise is growing, in part paralleling the simultaneous release of unprofitable enterprises. The number of enterprises with large vine areas is growing in the areas with full-time enterprises as well as those with part-time enterprises. In the south-west in contrast, vine cultivation is increasingly disapearing from farm size classes 3 to 7,5 ha. and family enterprises over 7,5 to 10 ha. are concentrating primarily on building up their total use area, with vine area in second place. Relatively few farmers see viticulture as their main enterprise product. Only in part-time enterprises can a certain concentration on viticulture be ascertained. In the contracting vine areas, the widespread planting of other agricultural products eased the release of vine areas for larger farms. This alternative is lacking in the Mosel, Ahr and middle Rhine wine areas. Here, the wine-growers only have the possibility of extending their vine area or changing their primary occupation.